2005
DOI: 10.1111/j.1525-1438.2005.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 and Fas polymorphisms and susceptibility for (pre)neoplastic cervical disease

Abstract: Infection with oncogenic types of human papillomavirus (HPV) is the main causal factor of cervical cancer and its precursor lesion (cervical intraepithelial neoplasia [CIN]). Cellular immunity may be critical in the elimination of HPV-harboring cells. Interleukin-10, a T-helper type 2 cytokine, has a suppressive effect on cell-mediated immunity. Resistance to apoptosis through the Fas pathway might enable many cancers to escape the immune system. We examined in a large study population whether three polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
5
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 35 publications
5
62
5
2
Order By: Relevance
“…There was no association for the SNP at position 21082 and no difference in the distribution of haplotypes between cases and controls. 22 In their dataset, the polymorphism at position 2819 showed strong linkage disequilibrium (LD) with position 2592, in agreement with several previous reports claiming that these SNPs make up the three major haplotypes GCC, ACC and ATA (21082, 2819, 2592). [22][23][24]50 An earlier study on 77 patients with cancer and 69 controls reported an increased risk of cervical cancer for subjects carrying the 21082 G allele in the Shona ethnic group of Zimbabwe.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…There was no association for the SNP at position 21082 and no difference in the distribution of haplotypes between cases and controls. 22 In their dataset, the polymorphism at position 2819 showed strong linkage disequilibrium (LD) with position 2592, in agreement with several previous reports claiming that these SNPs make up the three major haplotypes GCC, ACC and ATA (21082, 2819, 2592). [22][23][24]50 An earlier study on 77 patients with cancer and 69 controls reported an increased risk of cervical cancer for subjects carrying the 21082 G allele in the Shona ethnic group of Zimbabwe.…”
Section: Discussionsupporting
confidence: 77%
“…22 In their dataset, the polymorphism at position 2819 showed strong linkage disequilibrium (LD) with position 2592, in agreement with several previous reports claiming that these SNPs make up the three major haplotypes GCC, ACC and ATA (21082, 2819, 2592). [22][23][24]50 An earlier study on 77 patients with cancer and 69 controls reported an increased risk of cervical cancer for subjects carrying the 21082 G allele in the Shona ethnic group of Zimbabwe. 21 A third study investigated the 3 promoter polymorphisms using 144 Korean patients with invasive cervical cancer and 179 controls and does not detect any association; the 21082 position is not polymorphic in the Korean population.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations